Phytoplankton Diversity in Relation to Physico-Chemical Parameters of Gnanaprekasam Temple Pond of Chidambaram in Tamilnadu, India - M. Selvaraju, K. Thirugnanamoorthy (Recent Research in Science and Technology, 2009)
Twelve physico-chemical parameters, diversity and abundance of phytoplankton of fresh water pond of Chidambaram have been studied during September 2007 and August 2008. A total of 14 phytoplankton genera, 4 belonging to cyanophyceae, 4 to chlorophyceae, 3 to Bacilariophyceae and 3 to Euglenophyceae were recorded. To know to the variations in Periodicity and distribution of phytoplankton, various physico-chemical and biological parameters of the pond water have been observed. The values of TDS, BOD phosphate and nitrate and the current status of phytoplankton population imply that the study pond are mesotrophic in nature.